Optimizing the Updating Stopping Condition for a Predictive Maintenance Policy (Journal of Modern Mechanical Engineering and Technology, 2014)
The updating stopping condition (USC) has great impact on the effectiveness of a predictive maintenance (PdM) policy, but did not receive enough attention. This paper reviews the common USCs, proposes a residual life based USC, and evaluates the influence of the USCs on the effectiveness of a PdM policy. The commonly used USCs are concretely defined in a PdM policy based on the stochastic linear degradation model. An extensive numerical investigation compares the performances of the PdM policy using different USCs. The investigation results verify the importance of optimizing the USC for a PdM policy.